듣기이해능력 향상에 영향을 미치는 요인에 관한메타분석연구 - 김현정; 맹은경 (영어영문학연구, 2018)
Many experimental studies have reported factors affecting English listening comprehension in Korea. However the reported results do not specifically deal with how effective the factors are in improving English listening comprehension. This quantitative meta-analysis study, therefore, aims to investigate the effectiveness of the factors (vocabulary, sound discrimination, syntactic ability, background knowledge, and listening strategy) on the improvement of listening comprehension in Korean EFL classrooms. A total of 117 studies with 133 samples were collected, and their effect sizes (ES) were calculated based on Hedge’s g with the CMA software (ver. 2.2.056). The results of this study showed that syntactic ability had the greatest effect on listening comprehension (ES=.816, p=.012). Vocabulary learning (ES=.421), sound discrimination training (ES=.453), grammar education (ES=.816), activation of background knowledge (ES=.599), and listening strategy training (ES=.498) all contribute to effectively improving listening comprehension regardless of the age of Korean EFL learners. In addition, the length of listening instruction did not affect listening comprehension. Based on the findings, pedagogical suggestions are also discussed.
Keywords: 메타분석; 메타회귀분석; 듣기이해; 어휘력; 배경지식; 통사적 능력; 듣기전략; 음의 식별력; meta-analysis; meta-regression; listening comprehension; vocabulary; sound discrimination; syntactic ability; background knowledge; and listening strategy